Cross-border and ideology: a decolonial perspective of literature in the East Dutch Indies era - Sulistyo, Hary; Faruk, Faruk; Sudibyo, Sudibyo (Institut Seni Indonesia Surakarta, 2025)
This paper explores the representation of cross-border and cross-ideological narratives in literary and dramatic works from the Dutch East Indies era. It focuses on five categories: Dutch, Indies, Peranakan-Tionghoa, Balai Pustaka, and non-Balai Pustaka Bumiputera literature. The study aims to: (1) classify these works based on racial and ideological markers; (2) analyze how identity and ideology are represented within each category; and (3) examine how counter-knowledge and resistance to colonial discourse are articulated in the texts. Using a descriptive qualitative method, the research involves close reading of texts to identify identity representations, gathering contextual data on authorship, and analyzing ideological patterns across categories. Findings reveal that Dutch and Indies authors often construct Native characters through a Western, objectifying lens, reinforcing colonial hierarchies. In contrast, non-Balai Pustaka Bumiputera writers frequently resist these narratives, offering critical perspectives on racism and colonial subjectivity through localized, spiritual, and humanistic views. The study further identifies how Western literary discourse relegates Native works to the “Batjaan Liar” (wild reading) category, while Eastern narratives challenge imperialist classifications. While authorial ideology often aligns with racial or institutional affiliation, some texts reveal ideological divergence. Ultimately, this research contributes a decolonial perspective that critiques Western modernity’s portrayal of the Native, going beyond conventional postcolonial approaches that focus primarily on colonial impact. It emphasizes the importance of Indigenous resistance and epistemology in shaping literary discourse during the colonial period.